The act of eating. - Khoo, Li Ying. (2009)
In art, film and literature, the act of eating is a frequent subject which serves two broad functions: to illustrate individuality and to examine concepts related to community. At the individual level, the process of eating and its consequences are often used as a metaphor for concepts such as basic survival, personal transformation and individual identity. At the community level, the preparation and consumption of food represents interaction, communication and culture, making food a rich metaphor for issues which fall under these areas. This project thus identifies the act of eating as both an individual and universal process, and presents the act in a visual form that parallels this process. This is done through an approach which alludes to the digestive process. In the digestive process, food is broken down into its parts before being assimilated into something larger: life itself. Similarly in this project, the act of eating is broken down and examined in parts: the two areas of Consuming and Communing. Consuming deals largely with the individual aspects of eating, whereas Communing looks at the function of food in communication and interaction. In accordance with the method, material is collected from individuals and combined to form pieces larger and more cohesive than the individual contributions themselves. This project thus creates awareness in the world of the individual yet universal properties of food, bringing it from the realm of food as related to subtopics, to food as related to itself. It is thus partly an artistic project and a sociological study put into visual form.